The Effect of Online Collaborative Writing through Edmodo on Students’ Writing Skill at MA Masyhudiyah Giri - Tasri, Merinda Fiana (Journal of English Teaching, Literature, and Applied Linguistics, 2021)
Implementing a writing strategy especially collaborative writing is one of the efforts to make writing learning work optimally. In its application, collaborative writing strategy is claimed to have a positive effect on each aspects of student writing skill, but based on the implementation of this strategy, several problems are found, where students are still less active in discussions and students do not want to be involved in the collaborative writing process. So with these problems, it certainly becomes an obstacle that can cause the implementation of this strategy do not run optimally, so that the selection of a media is the right way to overcome these problems by using Online Learning based Edmodo. The design of this study was quasi experimental design, with 10th grade students from MA Masyhudiyah as the subject. Two classes were chosen, they were X-MIPA 1 as an experimental class and X MIPA 2 as a control class with 28 students in each class. The research findings in this study revealed that there were significant differences between the experimental and control groups. This is evidenced by the results of sig. (2-tailed) is 0,000. The sig. (2-tailed) is lower than the significance level of 0.05 (0.000 <0.05). So, the null hypothesis (Ho) can be rejected. So it can be interpreted that Online Collaborative Writing through Edmodo has a positive effect on students' writing skills. Therefore, the researcher strongly recommend to the teachers to apply Online Collaborative Writing through Edmodo in the teaching and learning process and also for further researchers can conduct similar research in other ways, skill or levels.